Menstrual Hygiene Management (MHM) Education in Elementary School Students as the Implementation of Personal Hygiene Behavior during Menstruation - Heni Purwaningsih; Nurul Istiqomah; Sulastri Sulastri; Yuli Widyastuti; Ika Kusuma Wardani; Suyatno Suyatno (Peneliti Teknologi Teknik Indonesia, 2021)
Menstrual Hygiene Management (MHM) is the management of hygiene and health when women are menstruating. MHM components include the use and selection of sanitary napkins, frequency of changing sanitary napkins, management of single-use sanitary napkins, and access to toilets, soap, and water for cleaning. The purpose of this activity is to provide education on menstrual hygiene management as the application of behavior to maintain personal and environmental hygiene during menstruation. This community service method is carried out online (online) using the Zoom application, by providing pre and post questionnaires to measure students' knowledge about MHM at SDIT Nur Hidayah Surakarta students. The results of community service activities (PkM) showed that the number of respondents were young women who were already menstruating at the age of 11-12 years as many as 36 students and most of them had experienced menstruation. Education is done using power point media (PPT) and animated videos. The results of the pre-test showed that the majority of young women's knowledge about MHM was in the less category of 63.9%, while the category was sufficient 22.2% and the good category was 13.9%. After the education was carried out, the level of knowledge of students increased. Most of them had good categories of 83.3% and 16.7% had sufficient category knowledge and no students had poor category knowledge. It is necessary to increase the role of teachers and parents to support the improvement of reproductive health at a young age as well as the provision of communicative information media for elementary school students.